Strategi Multidimensi Komparatif Global Dalam Transformasi Pelayanan Kesehatan Primer Di Negara Berkembang: Literature Review - I Wayan Nova Suandita (Universitas Ivet, 2026)
Primary healthcare plays a crucial role as the foundation of an equitable healthcare system, particularly in addressing resource constraints in developing countries. However, its implementation is frequently hindered by systemic barriers, such as inadequate infrastructure and fiscal disparities. This study aims to map the dynamics, challenges, and strategies for strengthening primary healthcare transformation in developing countries through a global comparative approach. The method employed is a literature review, evaluated using the PRISMA flow diagram model to screen articles published over the last five years (2021–2025). The literature search identified research articles across several databases: Google Scholar (n=16,400), PubMed (n=1,277), and ScienceDirect (n=18,123). Based on these databases, a total of 35,800 articles were retrieved. An initial identification based on titles that exactly matched this study resulted in 26,619 selected articles. Screening was then conducted, ultimately resulting in the selection of 5 final articles. The review findings indicate that primary healthcare transformation is multidimensional and encompasses five main pillars: accelerating the adoption of digital technology in rural areas, strengthening the fiscal management governance of local facilities, integrating post-pandemic mental health services, adapting public financing schemes for screening catastrophic diseases, and enhancing the operational resilience of healthcare workers during crises.